Research on deep geological structure and forecasting of some areas with petroleum prospects in the Red river delta coastal strip according to geophysical data - Vuong, Hoang Van; Kha, Tran Van; Hung, Pham Nam; Dung, Nguyen Kim (Vietnam Journal of Marine Science and Technology, 2019)
The coastal areas of the Red River Delta are the transition areas from the continent to the sea and have great mineral prospects, especially petroleum prospects. In this area, a lot of topics and projects in geology and geophysics have been conducted for many different purposes such as studying the deep structure, tectonic - geological features, seismic reflection - refraction to identify petroleum traps in the Cenozoic sediments... However there are very few studies on deep structure features, using the results of processing and meta-analysis of gravity, magnetotelluric, tectonic - geological data to detect the direct and indirect relations to the formation of structures with petroleum potential. The authors have researched, tested and applied an appropriate methodology of processing and analysis, to overcome the shortfall of gravity data as well as the nonhomogeneity in details of seismic and geophysical surveys. The obtained results are semi-quantitative and qualitative characteristics of structure of deep boundary surfaces, structural characteristics of fault systems and their distribution in the study area, calculation of the average rock density of pre-Cenozoic basement... From these results, the authors established the zoning map of the areas with petroleum potential in the Red river delta coastal strip according to geophysical data.